A Novel ARL3 Gene Mutation Associated With Autosomal Dominant Retinal Degeneration - Ratnapriya, Rinki; Jacobson, Samuel G.; Cideciyan, Artur V.; English, Milton A.; Roman, Alejandro J.; Sumaroka, Alexander; Sheplock, Rebecca; Swaroop, Anand (Frontiers in Cell and Developmental Biology, 2021)
Despite major progress in discovery of causative genes, many individuals and families with inherited retinal degenerations (IRDs) remain without a molecular diagnosis. We applied whole exome sequencing to identify the genetic cause in a family with an autosomal dominant IRD. Eye examinations were performed and affected patients were studied with electroretinography and kinetic and chromatic static perimetry. Sequence variants were analyzed in genes (n = 271) associated with IRDs listed on the RetNet database. We applied a stepwise filtering process involving the allele frequency in the control population, in silico prediction tools for pathogenicity and evolutionary conservation to prioritize the potential causal variant(s). Sanger sequencing and segregation analysis were performed on the proband and other family members. The IRD in this family is expressed as a widespread progressive retinal degeneration with maculopathy. A novel heterozygous variant (c.200A>T) was identified in the ARL3 gene, leading to the substitution of aspartic acid to valine at position 67. Asp67 residue is evolutionary conserved, and the change p.Asp67Val is predicted to be pathogenic. This variant segregated in affected members of the family and was absent from an unaffected individual. Two previous reports of a de novo missense mutation in the ARL3 gene, each describing a family with two affected generations, are the only examples to date of autosomal dominant IRD associated with this photoreceptor gene. Our results identifying a novel, pathogenic variant in ARL3 in a four-generation family with a dominant IRD augment the evidence that the ARL3 gene is another cause of non-syndromic retinal degeneration.